Stan i problemy zagospodarowania lasów w miastach województwa mazowieckiego - Młynarski, Wojciech; Kaliszewski, Adam (Leśne Prace Badawcze, 2013)
The article presents research on the management and supervision of forests located within cities in the Mazowieckie Province. The information was obtained from questionnaires sent to all 85 city authorities in the province. The questions were related to organization and supervision of forests, forest management and protection, recreational management and financing of forests, as well as main problems associated with the management of urban forests. The research indicated that forests, which altogether cover more than 10% of city area, have a very important function, despite the forest area per resident being very small. The difficulties in forest management may arise due to their highly fragmented distribution as well as the mixture of many different types of forest owners. Moreover, communal forests in the province’s smaller towns lack proper management and protection structures and lack recreational facilities as local infrastructure is poorly developed. These sort of activities are conducted only in larger municipalities. Most of the non-state owned forests within cities have simplified forest management plans,which counts as a big plus for the Mazowieckie Province when considered in the context of the whole country. Certain measures should be taken to improve the condition of urban forests in the Mazowieckie Province, and serve to preserve and protection these forests. It is fundamental that city governments should cooperate with as wide as possible a circle of interested parties, to undertake common activities in forests of various ownership types located within each given urban area. Additionally, all feasible sources of financing should be considered.